Abstract 196: Navigation Orientation of the Angled Tip of the Zoom 71 catheter around the Carotid Siphon - Miguel Litao (Stroke: Vascular and Interventional Neurology)
Introduction Aspiration thrombectomy has been one of the mainstays of treatment in stroke interventions. The Zoom71 (Z71) aspiration catheter is unique with its angled tip. This study describes the orientation of the angled tip as its navigated around the carotid siphon and its association with trackability. Methods Prospectively collected cases involving large vessel occlusions of the anterior circulation which were intervened upon using the Zoom71 aspiration catheter were retrospectively analyzed. 71 passes, among 50 patients, among 7 operators, were analyzed with respect to Zoom71 catheter tip orientation with respect to the following corners: “Corner 1”‐ posterior vertical to horizontal portion of cavernous segment, “Corner 2”‐ ophthalmic turn, and “Corner 3”‐ ICA terminus to M1. The catheter tip orientation Was described as “UP” vs “DOWN” with respect to the inner curve of each corner. We also took note of whether the tip was “caught up” in the aforementioned corners during navigation. Results There was no preferential angled tip orientation of the Z71 as its navigated around the carotid siphon: Corner 1 (posterior vertical to horizontal cavernous), 51% (N=36) UP vs 44% (N=31) DOWN, p= 0.54; Corner 2 (ophthalmic), 46.5%(N=33) UP vs 53.5% (N=38) DOWN, p= 0.55; Corner 3 (terminus to M1) 43.7% (N=31) UP vs 46.5% (N=33) DOWN, p=0.63. It was not caught up in Corner 1. It got caught up in Corner 2 in 15.5% (N=11) of passes. The UP orientation at Corner 2‐ with Z71 angled tip pointing towards the ophthalmic (away from the inner curve), was associated with getting caught in 21% (7/33) of passes vs 10.5% (4/38) for the DOWN orientation though this was not statistically significant, p= 0.22. It got caught up in Corner 3 in 4.7% (N=3/64) of passes. The UP orientation at Corner 3 was associated with getting caught in 6.5% (2/31) of passes vs 3% (1/33) for the DOWN orientation, p=0.52. Usage of Z88 as guide catheter may be associated with Z71 getting caught up less in Corner 2 compared to other guide Catheters, 9.3% (4/43) for Z88 vs 25% (7/28) for “Others”, p= 0.07. This also applied to corner 3, 0% for Z88 vs 11.1% (3/24) for “Others”, p=0.038. Conclusion There is no preferential orientation of the angled tip of the Z71 as it navigates around the carotid siphon. The DOWN orientation may allow for better trackability around the ophthalmic turn. Usage of Z88 as guide catheter may help with Z71 trackability around the siphon.